Serum Cytokines and Cancer in Involuntary Weight Loss. (1st June 2012) - Baicus, Cristian; Caraiola, Simona; Rimbas, Mihai; Patrascu, Ruxandra; Baicus, Anda
Abstract : Background: Tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β), and IL-6 may be associated with involuntary weight loss in patients with and without cancer. However, results of previous studies have been conflicting. We evaluated patients who had involuntary weight loss to determine cytokine levels and the correlation of these cytokines with weight loss, the association with inflammation, and the potential for use in cancer diagnosis. Materials and Methods: In 290 consecutive patients with involuntary weight loss (74 patients [26%] with cancer and 216 patients [74%] without cancer), erythrocyte sedimentation rate (ESR), and serum levels of C-reactive protein, TNF-α, IL-1β, and IL-6 were determined. Results: Higher ESR and levels of C-reactive protein, TNF-α, IL-1β, and IL-6 were associated with cancer. The levels of TNF-α, IL-1β, and IL-6 did not correlate with the amount of weight loss. In multivariable analysis, only ESR was associated with cancer. Conclusions: In patients with involuntary weight loss, TNF-α, IL-1β, and IL-6 were associated with cancer but were not weight loss mediators.